Vagrants and Beggars Countermeasures at Denpasar City in Criminology Perspective - Swardhana, Gde Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 9 No 1 (2020)DO - 10.24843/JMHU.2020.v09.i01.p02, 2020)
The purpose of this research article is to find out and analyze criminological problems with vagrants and begging. The problem of vagrants and beggars in Denpasar is very complex, related to legal, social, economic, mental, and cultural aspects of the community. Vagrants and begging are regulated in Articles 504 and 505 Criminal Act, also the Regional Regulation of the City of Denpasar No. 15 of 1993 jo. No. 3 of 2000 concerning Cleanliness and Public Order. This research is empirical law with document study and interview techniques. Analysis of legal materials using descriptive, argumentative, and evaluative. The result is found that the causes of vagrant and beggars are internal factors, namely poor living; age; Education; and mental attitude. External factors, namely: the condition of water demand; crop conditions for agriculture, and limited access to information and business capital. Related to the effort to overcome vagrant people and beggars include preventive, repressive, and rehabilitative efforts.